2004
DOI: 10.1016/j.jtcvs.2004.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic growth factors and/or cellular therapy for myocardial regeneration: A comparative study

Abstract: In the cell therapy groups, regional ventricular contractility improved and heart dilatation was limited compared with either vascular endothelial growth factor or control; thus, postischemic remodeling was reduced. Angiogenesis was demonstrated in the vascular endothelial growth factor group, without improvement of ventricular function and remodeling. To improve local conditions for cell survival, further studies are warranted on prevascularization of myocardial scars with angiogenic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 46 publications
2
33
0
1
Order By: Relevance
“…However, cardiac function improved after intramyocardial delivery of pAng1. Cell therapy using skeletal myoblast has been shown to be superior to VEGF protein therapy for myocardial regeneration [18]. In the present study, we demonstrated that cell therapy using hMSCs was superior to VEGF and Ang1 gene therapy in enhancing angiogenesis and improving cardiac function after myocardial infarction in mice.…”
Section: Discussionsupporting
confidence: 51%
“…However, cardiac function improved after intramyocardial delivery of pAng1. Cell therapy using skeletal myoblast has been shown to be superior to VEGF protein therapy for myocardial regeneration [18]. In the present study, we demonstrated that cell therapy using hMSCs was superior to VEGF and Ang1 gene therapy in enhancing angiogenesis and improving cardiac function after myocardial infarction in mice.…”
Section: Discussionsupporting
confidence: 51%
“…In animal models of MI, researchers have tried to combine gene and cell therapy but among five studies (Chachques et al 2004;Azarnoush et al 2005;Schuh et al 2005;Yang et al 2006), only 2 in which skeletal myoblasts transplantation was combined with HIF-1a gene therapy (Azarnoush et al 2005) or CD34+ cells injection were combined with VEGF-2 gene therapy (Shintani et al 2006) demonstrated enhanced therapeutic effects compared to cell or gene therapy alone.…”
Section: Combined Gene and Cell Therapy-mentioning
confidence: 99%
“…It is apparent that the exact mechanism is still to be elucidated, since early reports on differentiation of mobilized SCs into cardiomyocytes and endothelial cells in the infarcted area are challenged by recent experimental work. These studies reported a direct antiapoptotic effects of G-CSF on cardiomyocytes and endothelial cells in infarcted hearts as well as an accelerated wound healing process in the necrotic tissue along with the myocardial regeneration effect (Table 4) [80,81]. In a recent randomized trial by Zohlnhofer, after granulocyte colony-stimulating factor induced stem cell modilization in acute myocardial infarction following successful coronary intervention, no increase in ejection fraction or a decrease in infarct size was seen [82].…”
Section: Mobilization Of Stem/progenitor Cellsmentioning
confidence: 99%
“…Stem and progenitor cell mobilization, with granulocyte colony-stimulating factor (G-CSF) and/or stem cell factor (SCF) and other cytokines has been shown to improve cardiac function after MI in the experimental setting [73][74][75][76][77][78], but results do not seem to be uniform in different species [79] or even in different patient groups [80]. It is apparent that the exact mechanism is still to be elucidated, since early reports on differentiation of mobilized SCs into cardiomyocytes and endothelial cells in the infarcted area are challenged by recent experimental work.…”
Section: Mobilization Of Stem/progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation